Impact of growth mindset intervention (GMI) in attitude towards maths among secondary school students - Mohd Noh, Noor Atiqah; Ma’rof, Aini Marina; Mohamad Yusof, Yusni (Global Academic Excellence, 2023)
Attitude toward maths is shaped by cognitive components such as beliefs and perception. By having a positive attitude, students are more likely to embrace challenges, seek out new opportunities to learn, and develop resilience in the face of setbacks. This can open doors to a wide range of career opportunities and improve academic performance. Therefore, this study aimed to investigate the impact of a growth mindset intervention (GMI) on secondary school students' attitudes towards maths by using quasi-experimental design. A total of 69 form two students from two secondary schools in Kedah, Malaysia participated and were randomly assigned to the control (n=35) or treatment group (n=34). The GMI module, consisting of seven sessions covering seven topics, was implemented in the treatment group. Data were analyzed using descriptive and inferential statistics in SPSS Version 26. Descriptive analysis indicated that the respondents had a moderate level of attitude towards maths. To evaluate the effectiveness of the intervention, Multivariate Analysis of Covariance (MANCOVA) was used, while controlling for covariate variables such as math's score and gender. The results showed a significant improvement (p < .05) in the treatment group's attitudes towards maths compared to the control group in the post-test. This study highlights the importance of creating a growth-mindset-oriented classroom environment and integrating growth mindset elements into maths teaching to enhance students' beliefs about their abilities and intelligence.